Hyolmo in Oralities and Ethnographies: An Intimate Reflection - Lama, Wangyal (Nepal Journal of Sociology, 2025)
The purpose of this reflective essay is to share three meaningful observations intended to elucidate for those readers who are interested in Hyolmo. Presenting the Hyolmo community is, of course, the first step. The next involves a brief overview of the body of work produced by Western scholars. Lastly, I intertwine my personal experiences as a member of the Hyolmo community with my feelings and views on these written representations that have developed since the 1970s. A son of a Lama who was raised in the Beyul beliefs, later assimilated into an alien educational system. This transition disrupted the values and beliefs of my upbringing; nonetheless, it caused me to connect more with the latter, ultimately shaping my hybrid identity. This soul-searching mental state prompted me to express my thoughts, which is why I regard this text as an intimate reflection. Within it, I weave together my personal journey with my community’s culture, history, belonging, continuity, transformations and representation of these elements in the scholarly texts– urging me to draw upon, engage with and interpret Hyolmo folklore and orality, alongside ethnographic and Tibetological works. Moreover, this reflection makes clear that a group culturally known as Lama and Sherpa transformed into a separate identity as Hyolmo, to adapt and integrate within the identity claims and claim-making processes that arose following the political dynamics of the 1990s.